EFFECTIVE TEACHING OF READING IN EDUCATION. - Shodmonova Shakhnoza; Omonova Nodirabegim; Gaforov Iqboljon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. In our attempts to improve reading instruction we have had hundreds of studies of the characteristics of pupils, and scores of studies in which instructional programs and materials have been compared, but there have been surprisingly few studies of the teacher's contribution--of the teacher characteristics that make for successful learning, or of specific forms of teacher behavior that are associated with good and poor pupil learning in the reading program.